“Even Though He Had Expressed Willingness to Take PrEP, He Declined When He Noticed the Drugs Were Packed in a Container Like That of ARVs”: Exploring Barriers to HIV/AIDS Risk Reduction Among Long-Distance Truckers in Kenya - Cyrus Mutie MSc; Kawira Kithuci PhD; John Gachohi PhD; Grace Mbuthia PhD (Journal of the International Association of Providers of AIDS Care)
Abstract Background Due to high-risk sexual networks along their transit routes, Long-distance truckers’ (LDTs) risk of HIV is known to be high, as evidenced by prevalence rates of 14.34% in the region. Besides, the spaces in which LDTs operate are often marred with a multitude of barriers to HIV/AIDS risk reduction. However, there is limited evidence on the barriers encountered by LDTs in Kenya, hence the need for the current study. Methods and Methodology We used nine key informants and 18 in-depth interviews from purposively sampled participants, such as nurses and LDT peer educators at Kenya's Busia and Namanga international border points. We used semi-structured interview guides to collect data through audio records. Interviews were transcribed, coded, and thematically analysed using the QDA-Miner software to generate themes and sub-themes around barriers to HIV/AIDS risk reduction among LDTs. Findings Overall, three themes, namely, health system, individual-level, and trucking career-related barriers emerged. The sub-themes under health system barriers included the location of healthcare facilities far from transit routes, long durations of hospital waiting time, and lack of targeted health facilities for LDTs, among several others. Under trucking career-related barriers, the sub-themes comprised tight work schedules, unfavourable trucking career policies, and insecurity along transit routes. For individual barriers, some of the sub-themes were language barriers and lack of awareness of current HIV/AIDS risk reduction services. Conclusion Alongside health system factors, individual level and trucking career-related factors were highlighted as the barriers to HIV/AIDS risk reduction among LDTs in Kenya. The existence of these barriers may complicate the fight against the pandemic in this hard-to-reach population, given their already known vulnerability to HIV infections.